Towards an interdisciplinary approach to introduce economic modelling in Secondary Education: a proposal on the derivative and the marginal analysis - Gutiérrez-Portilla, María; Gutiérrez-Portilla, Paula; Álvarez-Causelo, Pedro (IJERI: International Journal of Educational Research and Innovation, 2021)
The paper describes a virtual learning object (VLO) built under an interdisciplinary perspective integrating Economía and Matemáticas aplicadas a las Ciencias Sociales, which are both subjects within the Humanidades y Ciencias Sociales area in Bachillerato. Such VLO is created out of a sequence of applications designed in the software Geogebra and organized around the mathematical concept of the derivative function and its role as an essential tool in economic modelling (mainly linked to what is usually known as marginal analysis). The proposal aims to exemplify a set of materials and activities that could be designed and used in an integrated way by teachers of both subjects. From the viewpoint of teaching Economía, this type of approaches may facilitate the transfer of mathematical knowledge to the field of economic modelling, which is especially relevant when taking into consideration the propaedeutic purpose of Bachillerato. Concerning the teaching in Matemáticas, research on its didactics as well as the curriculum content for the Educación Secundaria Obligatoria (ESO) and Bachillerato highlight the dual goal of developing students’ modelling competency and enhancing their learning of the mathematical concepts involved.